Solar Energy Policies for Commercial Buildings in India: Perspective of Government Officials. (September 2022) - Jain, Meenal; Mital, Meenakshi; Syal, Matt
India is a developing nation with urban populations growing exponentially and rural villages being electrified. Thus, India is expected to have a high growth rate in energy demand over the coming years for which the nation is heavily dependent on fossil fuels. Solar energy presents an attractive solution to growing energy challenges as it is abundant, inexhaustible and environment friendly. Many programmes and policies have been initiated at both the national and state level for promoting solar energy across all sectors. This article comprehensively assesses various government initiatives for off-grid solar photovoltaic (SPV)/solar water heating (SWH) systems for commercial establishments and brings forth the government perspective in terms of implementation of these initiatives, need for improvements and the lacunas in availing the incentives. The article also presents suggestions given by government officials for better acceptance and implementation of such initiatives.